Application of Criminal Consequences in Cases of Breach of Contract Agreement If the Case Cannot Be Resolved Civilly - Nurpasa, Wibowo; Gunarto, Gunarto (UNISSULA Semarang, 2025)
Abstract. This research is motivated by the occurrence of a case of default which is a civil law case but the case cannot be resolved civilly so that other efforts such as criminalization are needed. However, whether the application of criminal consequences in cases outside of criminal law can be done, this requires clear legal certainty in resolving this case because if it is not resolved it can cause injustice to other parties. The research conducted by this author uses a Juridical Sociological approach. The research specifications in this study include descriptive analysis research types. There are two types of data in this study, namely primary and secondary data. The research was conducted at the Kuningan District Court Office. The data collection method used is direct field study and literature study. The data obtained is processed using qualitative analysis. If done in good faith if one party does not fulfill its obligations then this is a civil breach of contract so that it cannot be categorized as fraud. If the agreement contains bad faith in the contract agreement then it can be categorized as getting criminal consequences. Criminal consequences in cases of breach of contract can only be carried out if the case does not yet have permanent legal force. The case of breach of contract agreement that is carried out contains elements of fraud in the agreement that occurs can be criminalized legally according to applicable laws. However, agreements made in good faith cannot be punished. If forced to get an onslag decision. Criminal consequences in cases of breach of contract can only be carried out if they do not yet have legal force.